PATRIOTISM AS REFLECTED IN THE MOVIEARGO - Al Hadawiyah, Azzahra Noor Hawa (LANTERN (Journal on English Language, Culture and Literature), 2016)
This thesis will discuss patriotism acts reflected by the characters of the movie ARGO. The movie tells about Tony Mendez a CIA agent who tries to save the staff of U.S. Embassy hostage in Iran by making a fake movie entitled ARGO. The objectives of this thesis are to describe the intrinsic aspect which covers the narrative elements and cinematic elements on the movie ARGO and explain the extrinsic aspect which covers the patriotism acts performed by the characters of the movie, especially Tony Mendez, John Chamber and Leister Siegel based on Patriotism theory by Igor Primoratz. The writer uses library research in collecting the data and uses sociology of literature approach. The result of this thesis find John Chamber, Leister Siegel and especially Tony Mendez showed modern patriotism by saving the six staff of U.S. Embassy in Iran from Iran militants. Meanwhile Iran militants represent group of people who have extreme patriotism.